Development of a microsatellite database for identification of olive (Olea europaea L.) cultivars in Mendoza, Argentina - Torres, M. R. (2014)
Olives were introduced in Argentina from Europe over 400 years ago. Severalcultivars are grown in Mendoza province and problems exist on misclassification ofplants in orchards and nurseries. This work was aimed to develop a cost effectiveprotocol for fingerprinting olive germplasm using microsatellites (SSRs) andgenerate a database in order to help in the identification of olives trees in Mendoza.Four highly informative polymorphic SSRs (DCA3, DCA9, DCA11 and DCA16)were selected to fingerprint olive cultivars. A protocol using a single dye-labeledforward common primer with the M13 (-21) sequence was used in combination withthe reverse specific SSR primers. PCR amplifications were multiplexed and resolvedin automated capillary genetic analyzer equipment. Profiles of the cultivars and alist of alleles with the sizes obtained by capillary electrophoresis are provided.Several genetic parameters were calculated to characterize the microsatellite loci. Adatabase of SSR markers for eleven of the more distributed olive cultivars inMendoza was developed.